Neurointerventional infusion of hemoglobin oxygen carrier prevents brain damage from acute cerebral ischemia in rats - Gao, Hong; Peng, Han; Yang, Hua; Li, Qiuping; Xiang, Xin (Frontiers in Surgery, 2023)
Aim: To save brain cells in acute cerebral infarction by injecting hemoglobin oxygen carrier (HBOC) into the blood vessel blockage of the cerebral infarction site through a microcatheter. Methods: 120 male rats were divided into four groups: control (CTRL), ischemia (I), ischemia + low perfusion (I + LP), and ischemia + high perfusion (I + HP). Perfusion groups (ischemia, I + LP, and I + HP) underwent MCAO surgery with intraluminal monofilament. These groups were subdivided into 6h, 12h, and 24h (n = 10/group). RT-PCR, Western-Blot, immunohistochemistry, and apoptosis assays were used to detect apoptosis, hypoxia range and extent, and ischemia. Results: Compared with the I group, the neurological deficit sign scores of the I + HP group were statistically significant at 12h. Compared with the I group, the neurological deficit sign scores of the I + LP group and the I + HP group were statistically significant at 24h. At all time points, compared with the I group and the I + LP group, Caspase-3, HIF-1α, and Cytochrome C protein levels were significantly decreased in the I + HP group. Bcl-2 and BAX mRNA levels were also significantly decreased in the same group. TNF-α, IL-6, and IL-1β cytokines were significantly decreased in the I + HP group as well. The infarct size of rats in the I + HP group was smaller than that of the I + LP group, which was smaller than ischemia alone. Time of perfusion had an obvious effect as infarct size was smaller with longer perfusion. The number of Nissl stained cells in the I + HP group was increased compared with the ischemia and the I + LP group, and was proportional to the time of perfusion. Conclusion: Time- and rate-controlled perfusion of HBOC to acutely occluded cerebral vascular regions through microcatheters can effectively protect ischemic brain tissue in rats.